Optimized deployment of drone base station to improve user experience in cellular networks. (15th October 2019) - Huang, Hailong; Savkin, Andrey V.; Ding, Ming; Kaafar, Mohamed Ali
Abstract: Modern wireless traffic demand pushes Internet Service Providers to develop effective strategies to improve user experience. Since deploying dense stationary base stations (SBSs) is not cost efficient, an alternative is to deploy drone base stations (drone-BSs) to supplement existing SBSs. We focus on the 3D deployment problem of drone-BSs to serve ground users in a given area. We formulate an optimization problem to find the optimal 3D positions for drone-BSs with the objective of maximizing the number of covered users, subject to the constraints that drone-BSs should be deployed at safe positions and the covered users receive acceptable Quality of Service. We analyze the difficulty of such a problem and show that it is NP-hard. A greedy algorithm is developed with computational complexity analysis. Extensive computer simulations are conducted to illustrative the effectiveness of the proposed algorithm and comparison with a baseline algorithm is provided to assess the performance gains.